Effects of TiO2 nanoparticles addition on dense bovine hydroxyapatite bioceramic on human odontoblasts - Fernandes, Paulo Henrique Martins (2021)
This study evaluated the effect of TiO2 nanoparticles on dense hydroxyapatite (HA) in human osteoblastic cells (SAOS-2). The natural source of HA was bovine bones. The experimental groups were performed from particulate HA powder with or without the addition of 5 or 8% TiO2 (DPBHA, DPBHA/AnataseNp5% or DPBHA/AnataseNp5%), pressed into discs (Ø = 12.5 mm; thickness = 1.3 mm) uniaxially (100Mpa) and isostatic (200 MPa/1 min) and sintered at 1300 °C. Y-TZP discs had exact HA dimensions. The tests performed were: (1) Scanning Electron Microscopy and Dispersive Energy Spectroscopy (SEM / EDS) (2) Atomic Force Microscopy (AFM); (3) biological tests using the Alamar Blue (AB) and Alizarin Red (AR) methods. Obtained data were tabulated and submitted to 2-way ANOVA and Tukey tests for the results of AB and ANOVA and Tukey tests for AR. SEM revealed that the surface of DPBHA/AnataseNp5% resembles DPBHA surface but also contains smaller granules and that the character of DPBHA/AnataseNp8% resembles DPBHA/AnataseNp5% surface, but with irregular topography and Y-TZP showed a typical oxide ceramics surface pattern. EDS revealed Ca, O and P in all HA composed samples with Ti in the reinforced ones, and C, O and Zr in Y-TZP samples. AFM data corroborates with SEM analysis. AB test revealed excellent cellular viability for DPBHA/AnataseNp5% group and AR test revealed that all groups containing TiO2np showed more mineralized matrix deposition than all other groups, with low statistical differences between reinforced groups and DPBHA cultivated in non-osteogenic medium and much bigger in osteogenic medium, with DPBHA/AnataseNp8% showing the best results. In conclusion, the addition of TiO2np showed chemical, superficial and biological changes in the reinforced materials, with the DPBHA/AnataseNp5% group being the one that showed the best results in cell viability and DPBHA/AnataseNp5% mineralized matrix deposition.